Metabolic dysfunction in obstructive sleep apnea: A critical examination of underlying mechanisms. Issue 1 (1st October 2014) - Mesarwi, Omar A; Sharma, Ellora V; Jun, Jonathan C; Polotsky, Vsevolod Y
Abstract It has recently become clear that obstructive sleep apnea (OSA) is an independent risk factor for the development of metabolic syndrome, a disorder of defective energy storage and use. Several mechanisms have been proposed to explain this finding, drawing upon the characteristics that define OSA. In particular, intermittent hypoxia, sleep fragmentation, elevated sympathetic tone, and oxidative stress – all consequences of OSA – have been implicated in the progression of poor metabolic outcomes in OSA. In this review we examine the evidence to support each of these disease manifestations of OSA as a unique risk for metabolic dysfunction. Tissue hypoxia and sleep fragmentation are each directly connected to insulin resistance and hypertension, and each of these also may increase sympathetic tone, resulting in defective glucose homeostasis, excessive lipolysis, and elevated blood pressure. Oxidative stress further worsens insulin resistance and in turn, metabolic dysfunction also increases oxidative stress. However, despite many studies linking each of these individual components of OSA to the development of metabolic syndrome, there are very few reports that actually provide a coherent narrative about the mechanism underlying metabolic dysfunction in OSA.